Astragalus taledensis, a new species of Leguminosae from Xinjiang, China - Zhang, Huan; Ren, Shanshan; Yan, Ping (Phytotaxa, 2021)
A new species, Astragalus taledensis P. Yan & H. Zhang (Leguminosae), is described from Xinjiang Province, China. Astragalus taledensis is distinguished from other species of Astragalus by its simple leaf, prostrate stem and the type of the legumes. The stamens of A. taledensis are nearly equal in shape and length, which is similar to some species of A. sect. Ornithopodium (eastern group). The species is most similar to Astragalus hamiensis S. B. Ho, from which it differs for the simple leaf, prostrate stem, length of the flower, bract and calyx, and width of the legume.